Fluoride-assisted detection of glutathione by surface Ce3+/Ce4+ engineered nanoceria. Issue 47 (23rd November 2022) - Patel, Vaishwik; Jose, Linta; Philippot, Gilles; Aymonier, Cyril; Inerbaev, Talgat; McCourt, Luke R.; Ruppert, Michael G.; Qi, Dongchen; Li, Wei; Qu, Jiangtao; Zheng, Rongkun; Cairney, Julie; et al.
Abstract : Nanoceria prepared with different Ce 3+ /Ce 4+ ratios show different oxidase mimetic activities. The activity is enhanced selectively in presence of fluoride ions and used for glutathione detection. Abstract : Nanoceria has evolved as a promising nanomaterial due to its unique enzyme-like properties, including excellent oxidase mimetic activity, which significantly increases in the presence of fluoride ions. However, this significant increase in oxidase activity has never been utilised as a signal enhancer for the detection of biological analytes partly because of the lack of understanding of the mechanism involved in this process. In this study, we show that the surface oxidation state of cerium ions plays a very crucial role in different enzymatic activities, especially the oxidase mimetic activity by engineering nanoceria with three different surface Ce 4+ /Ce 3+ compositions. Using DFT calculations combined with Bader charge analysis, it is demonstrated that stoichiometric ceria registers a higher oxidase mimetic activity than oxygen-deficient ceria with a low Ce 4+ /Ce 3+ ratio due to a higher charge transfer from a substrate, 3, 3′, 5, 5′ tetramethylbenzidine (TMB), to the ceria surface. We also show that the fluoride ions can significantly increase the charge transfer from the TMB surface to ceria irrespective of the surface Ce 4+ /Ce 3+ ratio. Using this knowledge, we first compare the fluoride sensing properties of nanoceria with high Ce 4+ and mixed Ce 4+ /Ce 3+ oxidation states and further demonstrate that the linear detection range of fluoride ions can be extended to 1–10 ppm for nanoceria with mixed oxidation states. Then, we also demonstrate an assay for fluoride assisted detection of glutathione, an antioxidant with elevated levels during cancer, using nanoceria with a high surface Ce 4+ /Ce 3+ ratio. The addition of fluoride ions in this assay allows the detection of glutathione in the linear range of 2.5–50 ppm with a limit of detection (LOD) of 3.8 ppm. These studies not only underpin the role of the surface Ce 4+ /Ce 3+ ratio in tuning the fluoride assisted boost in the oxidase mimetic activity of nanoceria but also its strategic application in designing better colourimetric assays.